Digital inclusion and parity: Implications for community development. Issue 1 (1st January 2021) - Gallardo, Roberto; Beaulieu, Lionel Bo; Geideman, Cheyanne
ABSTRACT: This paper introduces the concept of digital parity – similar levels of connectivity, devices, and skills between groups – that can lead to more digital inclusive communities. Utilizing a household survey measuring digital inclusiveness and ANOVA analysis, findings suggest that there are different levels of digital inclusiveness between groups. Differences in internet use and benefits are larger between younger and older groups. There are also differences between urban and rural areas. A statistically modeled digital parity scenario still finds uneven levels of digital inclusiveness, though urban and rural differences disappear, implying deeper and more complex inequality issues are at play. Future research should gather nationally representative survey data and see if findings hold. Regardless and as shown by COVID-19, community development practitioners need to incorporate digital inclusion strategies to ensure their communities transition to, adapt, and prosper in a sustainable way in this unfolding digital age.